If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10x + -4 = 11 + -7x Reorder the terms: -4 + -10x = 11 + -7x Solving -4 + -10x = 11 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -4 + -10x + 7x = 11 + -7x + 7x Combine like terms: -10x + 7x = -3x -4 + -3x = 11 + -7x + 7x Combine like terms: -7x + 7x = 0 -4 + -3x = 11 + 0 -4 + -3x = 11 Add '4' to each side of the equation. -4 + 4 + -3x = 11 + 4 Combine like terms: -4 + 4 = 0 0 + -3x = 11 + 4 -3x = 11 + 4 Combine like terms: 11 + 4 = 15 -3x = 15 Divide each side by '-3'. x = -5 Simplifying x = -5
| -5x-4x+7=-5 | | 2x^4+18x^2+243=0 | | 5x+4x-8=1 | | 17+8-20=4(a-7)-3 | | 11-5= | | 4(2x-10)=-10(x-5) | | 3x+243=12x-9 | | 2x^4+18x^2-243=0 | | 218-2x=43x+23 | | Y=2x^2-16x+25 | | 17+2b-4c=4(a-7)-3 | | 192-6x=6x+12 | | y*12=-60 | | 7x+5-5x-2=11 | | 5a=0 | | 2x+2y+3z=3 | | 5y=13 | | -2x-5=x+7 | | -2w=-0,5 | | 4n^2-3n-13=0 | | 22(-c)=-66 | | 12-5x=2x^2 | | 33-16=8-16+5a+5 | | 12*5= | | (2x+1)(3x-8)=(5x-24)(2x-5)-192 | | 28-4a=6(2a-2)+24 | | 5x+1=2x+22 | | 0.80x-0.40(60+x)=-0.20(60) | | -5u-(-4)= | | x*2=7x | | 7(a-4)-2a=19+3(a+3) | | 0.04y+0.12(200-y)=0.34y |